Batetannga Village Community, Binuang District, Polewali Mandar Regency: The Value of Responsible Character Education in Sibali-Sipatambak Culture - Subhan Subhan; Krishna Thongkaew; Limpu I. Digbun (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: This research aims to find out whether there is a value of responsible character education in the Sibali-Sipatambak culture in the people of Batetannga Village, Binuang subdistrict, Polewali Mandar Regency, to find out what factors influence changes in the social characteristics of the Sibali-Sipatambak culture towards society. Methodology: This type of research is qualitative. The data source used is information originating from direct observation at the research location. Data collection was carried out using field research through centralized observation and interviews. Main Findings: The results of this research show that there is a value of responsible character education in the sibali-sipatambak culture in Batetannga Village. Sibali-sipatambak is mutual cooperation in Batetannga Village in lightening the workload based on the abilities and abilities of each individual, which is based on the principles of togetherness, cohesiveness, kinship and humanity are so deep in order to lighten the burden carried together. The factors that influence changes in the socio-cultural characteristics of Sibali-Sipatambak influenced by cultural factors, modern technology, the increasing economic needs of the community and increasingly difficult life challenges. Novelty/Originality of this study: The novelty of this research is that there is still little research that specifically explores the relationship between the value of responsible character education and the Sibali-Sipatambak culture in Batetannga, Binuang District Village, Polewali Mandar Regency. Therefore, there is a description of knowledge that needs to be filled in to understand how the values ​​of responsible character education are practiced in the Sibali-Sipatambak cultural context, as well as their impact on the formation of a society with environmental character.